Se eu morrer hoje, amanhã faz dois dias: sobre o estatuto da conduta de risco dos adolescentes envolvidos no tráfico de drogas - Mariana da Costa Aranha (2016)
This work intends to analyze risk-taking behaviors of adolescents in illegal drug trade taking into consideration these juveniles decisive position on hanging on to traffic, despite deaths imminence. Risk was approached from anthropology, which associates absence of rites of passage in present days to dangerous behaviors taken by the adolescents. In this perspective, adolescents, in absence of rites of passage, would invent their personal and lonesome rites to symbolize entrance in adult life, seeking knowledge about life, and not death, through risk-taking behaviors. From this anthropological read, we propose an approach to risk that takes into consideration subjective aspects, as well as political and social aspects that drive the juvenile to wrestle with death. Thus we analyzed the statement of the Other on present days and problematize the passage to adulthood facing the Other that doesnt exist, as stated by lacanian oriented psychoanalysis, as well as the isolation situation in which our suburban Brazilian youth is at, biggest homicide victims. We took the sentence enunciated by the juveniles If I die today, tomorrow will have been two days as an axis to raise issues about the effects of the Others desire in subjectivity, and the role of this private war fought between the adolescents, in which the groups memory seems to impose as a need of inscription. We, besides, investigate imaginary logic, where the equation me or the other to which the juveniles are imprisoned prevails, having as basis psychoanalysis take on aggressiveness and the reading of real superego, that drives youth to obey a harsh law. We use case excerpts and psychoanalytical conversation experience reports to elucidate the statement of risk